Netymology: From Apps to Zombies: A Linguistic Celebration of the Digital World
Composed of 100 bite-sized entries of 400 to 600 words each, Netymology weaves together stories, etymologies and analyses around digital cultures transformation, and creation, of words.Tom Chatfield presents a kaleidoscopic, thought-provoking tour through the buried roots of some of the digital ages most common terms: from the @ and Apple symbols, to HTML and Trojan horses, to the twisted histories of new forms of slang, memes, text messages and gaming terms.Theres also discussion of the trends behind digital words, and of the ways language itself is being shaped by new forces and revelations about how these forces are, in turn, reshaping us.